209k views
2 votes
I dont understand this at all. I really need help! ​

I dont understand this at all. I really need help! ​-example-1

1 Answer

2 votes

Hello!


\large\boxed{x^(4)}

Recall that:


\sqrt[z]{x^(y) } is equal to
x^{(y)/(z) }. Therefore:


\sqrt[3]{x^(2) } = x^{(2)/(3) }

There is also an exponent of '6' outside. According to exponential properties, when an exponent is within an exponent, you multiply them together. Therefore:


(x^{(2)/(3) })^(6) = x^{(2)/(3)* 6 } = x^{(12)/(3) } = x^(4)

User Brian Slesinsky
by
6.1k points